2017
DOI: 10.17165/tp.2017.1-2.13
|View full text |Cite
|
Sign up to set email alerts
|

Learner Responsibility and Homework Quality in Secondary EFL Blending

Abstract: IntroductionIt is unquestionable that we live in the age of technology. Being a teacher trainee, no sooner had I entered the classroom than I realised that banning gadgets in the classroom would not be possible. What is more, not only would it be impossible, but a very foolish thing to do, seeing how much students are attached to them.I immediately became interested in what we can achieve together with my students involving technology and the Internet in our classroom. Having had some previous experience with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
4
0
3
Order By: Relevance
“…Azonban a digitális fejlesztések megvalósítása a tagállamok feladata (Caena, 2014), tekintettel arra, hogy az egyes országok különböző mértékben tettek korábbi lépéseket ilyen irányú fejlesztésekre. A direktívát követő éves jelentésekből kiderül, hogy a hazai általános és középiskolákban tanulók átlagos mennyiségű digitális eszközzel rendelkeznek (EU, 2019), ugyanakkor a digitális eszközök birtoklásából nem következtethetünk azok értő, tanulási célú használatára (Fekete, 2017(Fekete, , 2020M. Pintér, 2019;Tóth-Mózer, 2017), mint ahogy arra sem, hogy az eszközöket birtokló, vagy azokhoz hozzáférő tanárok megfelelően tudják alkalmazni őket a diákok tanulásának segítésére (Czirfusz et al, 2020;Dringó-Horváth & Gonda, 2018;Öveges & Csizér, 2018).…”
Section: Pázmány Péter Katolikus Egyetem Angol Nyelvpedagógiai éS Fordítástudományi Tanszék; Eötvös Loránd Tudományegyetem Nyelvpedagógiaunclassified
See 2 more Smart Citations
“…Azonban a digitális fejlesztések megvalósítása a tagállamok feladata (Caena, 2014), tekintettel arra, hogy az egyes országok különböző mértékben tettek korábbi lépéseket ilyen irányú fejlesztésekre. A direktívát követő éves jelentésekből kiderül, hogy a hazai általános és középiskolákban tanulók átlagos mennyiségű digitális eszközzel rendelkeznek (EU, 2019), ugyanakkor a digitális eszközök birtoklásából nem következtethetünk azok értő, tanulási célú használatára (Fekete, 2017(Fekete, , 2020M. Pintér, 2019;Tóth-Mózer, 2017), mint ahogy arra sem, hogy az eszközöket birtokló, vagy azokhoz hozzáférő tanárok megfelelően tudják alkalmazni őket a diákok tanulásának segítésére (Czirfusz et al, 2020;Dringó-Horváth & Gonda, 2018;Öveges & Csizér, 2018).…”
Section: Pázmány Péter Katolikus Egyetem Angol Nyelvpedagógiai éS Fordítástudományi Tanszék; Eötvös Loránd Tudományegyetem Nyelvpedagógiaunclassified
“…A digitális eszközök hozzáértő használata összetett jelenség, az értő használat pedig nem következik az eszközbirtoklásból (Fekete, 2017(Fekete, , 2020M. Pintér, 2019;Tóth-Mózer, 2017).…”
Section: A Kutatás Elméleti Háttere Oktatás éS Technológiaunclassified
See 1 more Smart Citation
“…It has been reported that ICT use in education prepares learners for modern workplaces (Yelland, 2001), makes them more autonomous learners (Iding, Crosby, & Speitel, 2002), and technological devices emerge as lifelong learning tools for the learners (Inan & Lowther, 2010). On the other hand, it is the teacher who is responsible for the implementation of the integration, because owning devices neither suggests that their inclusion is meaningful (MDOS, 2016), nor can be linked to students' willingness to use them for learning purposes (Fekete, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The present study aimed to design and validate a questionnaire measuring the ICT literacy of one group of adult learners: Hungarian English majors. A number of factors support the idea of developing a measurement tool for Hungarian adult learners, such as the fact that the integration of ICT in the classrooms is a local variable (Caena, 2014); integration of devices is not evidently meaningful in Hungarian schools (MDOS, 2016); learners do not inherently like using technology for learning (Fekete, 2017); and teachers are urged to enrol in ICT training courses to receive training on modern, computer-assisted teaching methods ( € Oveges & Csiz er, 2018) in order to facilitate meaningful inclusion and a professional learning environment for students. Because little is known about tertiary students' ICT use in Hungary, the goal was to identify constructs that can help to measure the ICT literacy of Hungarian English majors, discover relationships between the constructs and describe how able and willing learners are to use ICT both in their free-time and in their learning processes.…”
Section: Introductionmentioning
confidence: 99%